2000
DOI: 10.1136/jmg.37.6.434
|View full text |Cite
|
Sign up to set email alerts
|

Five cases of isolated glycerol kinase deficiency, including two families: failure to find genotype:phenotype correlation

Abstract: Little is understood of the genotype/ phenotype correlations in X linked glycerol kinase deficiency (GKD) where most cases are caused by extensive deletions of Xp21, which often include genes flanking the GK locus. Few cases of isolated GKD have been investigated where the phenotype is not influenced by neighbouring genes. In this paper, we present the mutation data from four confirmed and one suspected case of non-deletion, isolated, X linked GKD and therefore extend the base of patients that can allow an ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 21 publications
(18 reference statements)
1
34
1
5
Order By: Relevance
“…RNA analysis proved that he had a mutation in the GK gene and thus the isolated form of GKD and not the complex form, as it is defined to be caused by deletion of different loci in the p21 region of the X chromosome. As the g.16835G4A mutation has recently been described in another patient with isolated GKD, normal creatine kinase activity and adrenal function, 10 it is unlikely that this mutation could explain the complex clinical picture in our patient. The possibility of another gene defect occurring together with the insertion in the GK gene cannot be excluded.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…RNA analysis proved that he had a mutation in the GK gene and thus the isolated form of GKD and not the complex form, as it is defined to be caused by deletion of different loci in the p21 region of the X chromosome. As the g.16835G4A mutation has recently been described in another patient with isolated GKD, normal creatine kinase activity and adrenal function, 10 it is unlikely that this mutation could explain the complex clinical picture in our patient. The possibility of another gene defect occurring together with the insertion in the GK gene cannot be excluded.…”
Section: Discussionmentioning
confidence: 74%
“…Several cases with a GK activity 45% have been reported earlier. Sargent et al 10 have described a C256R substitution in a patient with 12% GK activity. This amino-acid residue is located in a b-sheet close to domains involved in ATP binding, 22 and this may result in an enzyme with some residual activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown no correlation between genotype (mutations in the GK gene) and phenotype (symptomaticity) in affected individuals. For example, the same GKD mutation was observed in both a symptomatic and an asymptomatic individual [12], and this discrepancy was also reported in two brothers with the identical mutation [13]. The glycerol phosphorylating activity of GK in lymphoblastoid cell lines or fibroblasts from symptomatic and asymptomatic individuals was similar.…”
Section: Introductionmentioning
confidence: 64%
“…5 lists the steady-state mass isotopomer abundances of the non-essential amino acids Pro, glutamate and glutamine (Glx), aspartate and asparagine (Asx), glycine (Gly), serine (Ser), and alanine (Ala), at the end of passage 2. The mass isotopomers of amino acid fragments including Gly [12], Ser [12], Ser [23], Ser[123], Asx [12], Asx[234], and Asx[1234], displayed significant differences (4.0 to 6.0 times the biological standard error) between the GKoverexpressing cell lines and the wild type (p < 0.03, Fig. 5).…”
Section: Mass Isotopomer Abundancesmentioning
confidence: 99%